Regiodivergent Synthesis of Brominated Pyridylthiophenes by Overriding the Inherent Substrate Bias - Hosoya, Masahiro; Mori, Atsunori; Okano, Kentaro (Synlett, 2023)
A regiocontrolled functionalization of a pyridylthiophene scaffold was accomplished. Regioselectivity for deprotonation of the pyridylthiophene was switched by changing the reaction conditions, including the metal amide base and the solvent. Subsequently, in situ transmetalation and halogen dance on the corresponding organometallic species were controlled by additives and the reaction temperature, as well as by the above reaction conditions. This method successfully enabled the synthesis of four iodinated constitutional isomers from a single starting material, 2-(5-bromo-2-thienyl)pyridine.
Keywords: deprotonation; halogen dance; organometallic reagents; pyridylthiophenes; regioselectivity